A Systematic Review and Meta-Analysis of Combination Behavioral Interventions Co-Targeting Psychosocial Syndemics and HIV-Related Health Behaviors for Sexual Minority Men. Issue 6 (23rd July 2020) - Pantalone, David W.; Nelson, Kimberly M.; Batchelder, Abigail W.; Chiu, Christopher; Gunn, Hamish A.; Horvath, Keith J.
ABSTRACT: In the U.S., sexual minority men (SMM) are disproportionately affected by HIV. Interventions are needed to increase HIV prevention and treatment behaviors, especially among syndemically exposed SMM. In recent years, researchers have created and tested combination behavioral interventions co-targeting syndemics and HIV-related health behaviors. We evaluated that literature via systematic review and meta-analysis, identifying 44 trials targeting mental health symptoms, alcohol use, and drug use, as well as sexual risk behavior, antiretroviral adherence, and healthcare engagement. For the randomized controlled trials, we computed between-group, pre-post effect sizes and tested them via random-effects models. Results supported the efficacy of combined interventions with significant, small, positive effects for improving mental health and reducing substance use ( d = .20, CIs: 0.12, .29), and reducing sexual risk behavior and improving antiretroviral adherence ( d = .16, CIs: .03, .30). Stratification analyses indicate that longer (9+ sessions) and individual (vs. group) interventions resulted in stronger effects on syndemic but not health behavior outcomes. Intervention developers should attend to intervention intensity and format. More evidence is needed about the importance of additional factors, such as novel intervention targets and cultural tailoring, as well as broadening the focus to multi-level interventions to address both interpersonal and structural mechanisms of change.